Pathways of excellence in science and dance: lessons learned from a Portuguese case study - Araújo, Liliana S. (2009)
Many researchers are studying the early identification of exceptional individuals, expertise acquisition, personality, and the role of external catalysts, aspiring to explain their influence on the process of talent and expertise development. Researchers seek a deeper understanding of these exceptional individuals, using multiple methodologies and techniques, studying multiple contexts and domains, and focusing on multiple dimensions and constructs associated with excellence. Moreover, much psychological research on excellence takes a predominantly outsider perspective favoring quantitative inquiry, but little is really known about the experiences and personal meanings of exceptional individuals. In this study, we explored the insider perspective of being excellent. Using a case study approach, two dancers and two scientists were interviewed. A theoretically-oriented content analysis grid was constructed to assist data analysis. Overall, participants stressed personal characteristics such as extreme curiosity, persistence, and passion for their work as central features in nurturing and sustaining their motivation for practice, and also as key features of being an excellent performer. Additionally, intensive and hard work, discipline, and strong commitment were emphasized and other personal and contextual dimensions highlighted. Singularities and some reflections that emerged from this study are discussed.